Reflection of Ethnic Cultural Phenomena in Historical Atlas of Ukrainian Statehood - Oleh Chyrkov (Українознавство, 2016)
The author has researched the coverage of ethnic cultural phenomena in Historical Atlas of Ukrainian Statehood published in Lviv in 2013 by the Research and Production Company Maps and Atlases. The Atlas was published in the Ukrainian language and positioned as a popular scientific edition. The information found in the Atlas on ethnic cultural phenomena, which took place on the terrain of the Ukrainian part of Europe, was systematized, described, and generalized.